Nagorno-Karabakh Conflict in the Context of Changing Regional Geopolitics - S. I. Chernyavskiy (Проблемы постсоветского пространства)
The article analyzes the changes in the South Caucasus associated with the results of the Armenian-Azerbaijani hostilities in the fall of 2020. According to the author, a radical breakdown of the geopolitical configuration of the region took place. The long-term ethnopolitical conflict between Armenia and Azerbaijan is a thing of the past, the self-proclaimed Nagorno-Karabakh Republic (Republic of Artsakh) practically ceased to exist. For the first time in 30 years, Russian peacekeepers have returned to these lands. The role of Turkey, a longtime arbiter of Caucasian affairs, has been revived. An end has been put in the most important of the interethnic conflicts that have destroyed the USSR since the late 1980s. And it was Russia who did it.As a result, each of the two republics controls only its internationally recognized territories, while Karabakh continues to exist de facto under the control of Russian peacekeepers. The decisiveness of V. Putin, who took upon himself the rescue of the civilian population and the settlement of the conflict, his ability to “persuade” irreconcilable enemies to stop the war and agree with the subsequent “peacekeeping intervention” contributed to a noticeable increase in Russia’s prestige in the region. However, the role of an independent arbiter capable of solving “insoluble” problems is impossible without strong political, legal, economic and military positions in the region. Therefore, the expansion of the Russian presence in the Transcaucasus is a factor of strategic importance that meets the national interests of Russia. The author believes that given the dismissive and consumerist attitude of the ruling elite of Armenia towards Russia, the time has come to adjust the choice of strategic partners in the South Caucasus. Azerbaijan is actively cooperating with Russia in key areas of world politics. One of the examples is the creation on the initiative of I. Aliyev of new formats of trilateral diplomacy in the composition of Azerbaijan-Turkey-Russia and Azerbaijan-Iran-Russia. An equally significant example is cooperation with Baku within the framework of the “Caspian Five”.Taking into account the specifics of the “multi-vector” nature of the South Caucasian states, it is advisable to conduct constant monitoring of Russian approaches to relations with them from the point of view of equal and pragmatic cooperation. This will make it possible to avoid that the resulting vacuum will be occupied by other powers that have been making themselves known more and more in recent years. Therefore, it is vitally important for Moscow that the authorities of the South Caucasus take into account its political interests.